FAKTOR – FAKTOR YANG MEMPENGARUHI KEMUDAHAN PEMELIHARAAN TERNAK KAMBING KACANG DENGAN SISTEM SEMI INTENSIF DI DESA BORONGTALA KECAMATAN, TAMALATEA, KABUPATEN JENEPONTO - Ansar, Muhammad Aminawar, Ikrar Muhammad Saleh (Jurnal Ilmu dan Industri Peternakan, 2015)
ABSTRACT. Goat rearing of extensive and semi-intensive maintenance can be increased to maintenance intensive system, weight gain can reach 50-150 grams per day. So that productivity in livestock commodities goats can be increased compared to the traditional maintenance of extensive wear  patterns (Mulyono and Sarwono, 2005). Given this reality, it is important to have a business, both from the government, private sector, research and development community to pay more attention to the ease of semi-intensive farming. Therefore, it needs to look and pay attention to the factors that affect the community raising goats with semi-intensive system. This is the background of the research conducted under the title. The purpose of this study was to identify factors - factors that affect the ease of maintenance of goats nut with semi-intensive system in the village of Borongtala District, Tamalatea, Regency Jeneponto. This research was carried out for 2 months starting from the date of December 8, 2014 until the date of January 2, 2015 in the village of Borongtala, District Tamalatea, Jeneponto. This type of research is explanatory research that aims to explain the effect of the independent variable on the dependent variable. Analysis of the data used is inferential statistical analysis by multiple linear regression. The results obtained Partially factor of economic value (X1), adaptation (X2), capital (X3) land (X4) and feed (X5) significantly affects society as a semi-intensive farming (Y) where (Tarithmetic> T table. Simultaneously, the economic value factor (X1), adaptation (X2), capital (X3) land (X4) and feed (X5) significantly affects society as a semi-intensive farming (Y) where (F count> F table).